Peran Profitabilitas dalam Memoderasi Pengaruh Akuntansi Hijau, Kinerja Keuangan, dan CSR terhadap Nilai Perusahaan - Muhamad Ridho Hardian; Rino Rinaldo; Elvia Fardiana (Jurnal Aplikasi Perpajakan, 2025)
This study aims to determine the effect of green accounting implementation, environmental performance, and Corporate Social Responsibility (CSR) on company value with profitability as a moderating variable in coal sub-sector companies listed on the Indonesia Stock Exchange (IDX). This study uses a descriptive quantitative approach with secondary data. The population in this study includes all coal sub-sector companies listed on the IDX for the period 2020-2024, totaling 34 companies. The sample used was taken using purposive sampling and consisted of 5 companies. The analysis technique used in this study was moderation regression analysis. The results of this study indicate that the implementation of green accounting affects company value, while environmental performance has a negative effect and CSR has no significant effect. Profitability can moderate the relationship between green accounting and company value. However, profitability cannot moderate the relationship between environmental performance and CSR on company value. In addition, the simultaneous implementation of green accounting, environmental performance, and CSR affects company value.